Estudio socieconomico de los productos de yuca (MANIHOT ESCULENTA CRANTZ) del sector 6 de agosto del Cantón Valencia Provincia de los Ríos. - Alarcon Mendoza, Loide Lisseth (2015)
This research was conducted in the area August 6 Canton Valencia, located in the northern part of the province of Los Rios, with the following objectives: Identify the problems of producers to develop the cultivation of cassava, evaluate the productive performance have cassava farmers in the area August 6, identify the marketing channels of fresh cassava industry August 6 and determine the socio-economic conditions of farmers in the sector August 6, for which surveys were applied properly formulated 73 farmers in the sector, and analyzed using exploratory, descriptive and explanatory method, considered as important in the productive sector question: What is the main agricultural activity ?, What level of social study has? and economic What price do you sell the sack of cassava ?, the same as were tabulated and interpreted. An analysis of the results it was concluded: most farmers engaged in the production of cassava (92%) are living for over 15 years in the industry August 6 and in the same way they own cultivated land, 70% have only studied primary and 15% were self-educated, indicating a low level of academic preparation. It was also found that 89% of farmers supported from 1-3 household members to perform their daily productive activities, basic food ranges from $ 51 to $ 100 a week, plus 44% of homes in the Farmers are wooden and / or cane and 37% are mixed (wood, cane and / or cement), where there is electricity, water from various sources, most are mobile and public transport covers 100% the sector where the study was conducted, it should be noted that 47% of respondents are mobilized transportation owned motorcycle being the most common. However 64% of cassava producers whose main problem fluctuating price of the product, resulting in a deficit in performance on the earnings of farmers and that at present the price of a sack of cassava is between $ 7 to $ 8, value has been maintained about two years ago; however production costs sample cycle to cycle increase, making productive benefit decreases. All farmers use the same marketing channel, which is the intermediary; he who is responsible for receiving and transporting the product to market, and those usually depends on the financing of cassava. Moreover 100% of the farmers are not members of any agricultural association or agricultural training have attended, besides not having any affiliation to social security. Most farmers in the area under study, show that cassava production have achieved economic benefits and improved quality of life.